Review: Neuroprotective effect of herbal plant extracts against Parkinson's disease - Syifa Fitriyanda Salsabila; Widhya Aligita; Yani Mulyani (Jurnal Ilmiah Farmasi, 2021)
Background: Parkinson's disease (PD) is a progressive neurodegenerative disorder caused by the loss of dopaminergic neurons and the exist of alpha-synuclein aggregates in the substantia nigra pars compacta (SNpc). Among the various types of neuroprotective therapy, natural products are potential therapeutic agents for PD.Objective: The aim of this study is to describe the neuroprotective effect of herbal plant extracts against Parkinson's Disease (PD).Method: The search strategy was carried out on electronic databases, namely Google Scholar, ScienceDirect, and PubMed. There are 111 scientific journals that have been filtered into 20 scientific journals which are international journals published in the last 5 years (2015-2020). The keywords used include Parkinson's Disease, Neuroprotective Effects, Neuroprotection, Plant Extracts, Natural Products and Parkinson's Disease Model.Results: Several experimental studies have shown the neuroprotective ability of various plant extracts to protect against neurotoxicity, through several neuroprotective pathways including antioxidant activity, anti-inflammatory activity, and antiapoptotic activity.Conclusion: Herbal plant extracts have been shown to have strong neuroprotective effects, making them as potential drug candidates for prevention or treatment of Parkinson's Disease (PD). There are Mucuna pruriens, Centella asiatica, Camellia sinensis, Ginkgo biloba, and Uncaria rhynchophylla.Keywords: Parkinson's Disease (PD), neuroprotective, extract.Intisari Latar belakang: Penyakit Parkinson adalah gangguan neurodegeneratif progresif yang disebabkan oleh hilangnya neuron dopaminergik dan adanya agregat yang mengandung alfa-synuclein di substansia nigra pars compacta. Diantara berbagai jenis terapi pelindung saraf, produk alami merupakan agen terapi yang potensial untuk PD.Tujuan: Untuk menggambarkan efek pelindung saraf ekstrak tanaman herbal terhadap penyakit Parkinson.Metode: Strategi pencarian dilakukan pada database elektronik yaitu Google Scholar, ScienceDirect, dan PubMed. Terdapat 111 Jurnal ilmiah yang telah di saring menjadi 20 jurnal ilmiah dan merupakan jurnal internasional yang diterbitkan 5 tahun terakhir (2015-2020). Kata kunci yang digunakan diantaranya Parkinson’s Disease, Neuroprotective Effects, Neuroprotection, Plant Extracts, Natural Products dan Parkinson’s Disease Model.Hasil: Beberapa studi eksperimen menunjukkan kemampuan pelindung saraf dari berbagai ekstrak tanaman untukmelindungineurotoksisitas, melalui beberapa jalur pelindung saraf diantaranya aktivitas antioksidan, aktivitas antiinflamasi, dan aktivitas antiapoptosis.Kesimpulan: Ekstrak tanaman herbal terbukti memiliki efek pelindung saraf yang kuat sehingga menjadikannya sebagai calon obat potensial untuk terapi pencegahan atau pengobatan penyakit Parkinson, diantaranya ekstrak tanaman Mucuna pruriens, Centella asiatica, Camellia sinensis, Ginkgo biloba, dan  Uncaria rhynchophylla.Kata kunci: Penyakit Parkinson. pelindung saraf, ekstrak